Russian Baptism and Orthodoxy. By Constantine Prokhorov = Russkij baptizm i Pravoslavie. Konstantin Prochorov - Dudchenko, Andrei (Bogoslovskie razmyšlenija, 2017)
Book review: Russkii baptism i pravoslavie (Seriia "Dialog") [Russian Baptism and Orthodoxy (Series "Dialogue"]. By Constantine Prokhorov. Moscow: Izdatel’stvo BBI. 2017. Pp. 450. ISBN 978-5-89647-362-6